Assessment of atmospheric corrosivity on metals and its mitigation by green corrosion inhibitors in the Klang Valley, Malaysia - Binyehmed, Fadel Mohamed M.Ali (2018)
The severity of atmospheric corrosion has now become a considerable concern worldwide, and poses a serious threat to many building materials. Many works in this field have been conducted, particularly in tropical areas, but Malaysia has not received much attention, only appearing in a few researches. Based on the literature, Malaysia suffers from acid deposition, which is caused by different air pollution sources. Therefore, the corrosion of metals may accelerate in the country. This study was conducted to assess the atmospheric corrosivity in Klang Valley, Malaysia, and to mitigate the corrosion issue by taking the environment into consideration. Physicochemical characteristics (pH, Electrical Conductivity and Total Dust Fall) were determined, and samples collected at four locations with three sampling sites from August 2014 to July 2015, with one location being chosen as the background location. The samples were collected using a passive sampler consisting of a funnel and polyethylene bottle. The results of acid deposition showed that Klang Valley was slightly acidic with a mean of 4.71 ± 0.48. Shah Alam had the lowest pH values due to development in the area, urbanization, and traffic population. Meanwhile, Puchong—the background station—was less acidic. A mean electrical conductivity (EC) of 52.50 ± 36.03 μS cm-1 was observed in this study, with Puchong showing lower EC values indicating improved air quality, and Shah Alam exhibiting higher ones, which may be attributed to the strong contribution of air pollution. Furthermore, the mean of total dust fall concentration exceeded the Malaysian guideline; reaching 199.51 ± 90.31 mg m-2 day-1. An outdoor atmospheric corrosion test of four metals (Carbon steel, Mild steel, Aluminum and Copper) was conducted in five locations, namely Shah Alam, UPM U2 & U3, Puchong, and Putrajaya. The corrosion rates were determined using weight loss based on ISO 9226. The results of the corrosion rates reveal that Shah Alam had the highest corrosion rates for all tested metals, while the lowest rates of corrosion were recorded in UPM U3 and Puchong. The atmospheric corrosivity indicates that the time of wetness was 4600 hour/year (τ4), with a SO2 deposition rate of 7.26 μg m- 3 (P0), and a chloride deposition rate of 27.44 mg m-2 day-1 (S1). The findings of this study reveal that the corrosivity of steel, aluminum, and copper belong to category C3 (medium) according to ISO 9223, indicating that there is an agreement between environmental parameters and corrosion rate. The results of the correlation coefficient showed that all physico-chemical characterizations of the investigated metals such as time of wetness, and the deposition rate of sulfur dioxide and chloride, strongly affect corrosion rate. Corrosion mitigation was conducted using four natural products, namely Green Coffee Extract (GCE), Green Tea Extract (GTE), Pomegranate Waste Extract (PWE), and Doum Extract (DE). Corrosion rate and inhibition efficiency were determined using electrochemical methods (Tafel polarization) in artificial acid rain and with different concentrations of extracts and different temperatures. The findings showed that all the green corrosion inhibitors under study acted as good inhibitors for aluminum corrosion, with only PWE and DE showing adverse effects on carbon steel corrosion. The adsorption of these inhibitors onto the tested metals obeyed the Langmuir adsorption isotherm, while the adsorption of molecule inhibitors followed the Temkin isotherm. From the values of the standard free energy of adsorption, ΔGads, it can be observed that the adsorption process on the tested metal surface was spontaneous adsorption, and the enthalpy of adsorption ΔHads showed that GCE acted as physical adsorption and the others performed as chemical adsorption, but the relationship between inhibition efficiency and temperatures proved that some extracts could perform chemical and physical adsorption, which was further proven via the Temkin isotherm. The one-way ANOVA analysis revealed that temperature variation did not significantly affect corrosion inhibition, which may be attributed to the chemical components’ inhibitor that could have been physically or chemically adsorbed onto the metal surface. In addition, variation in concentration of green inhibitors significantly affected the inhibition efficiency of carbon steel and aluminum. Furthermore, a multifactorial analysis of variance showed that corrosion inhibit ion was greater for all inhibitors of carbon steel in comparison to that of aluminum.